(untitled) (Geologica Macedonica, 2015)
White opalized tuff from the locality “Strmoš”– Probištip, is dominantly consisted of amorphous SiO2 (over 90% mass), and a minor quantity of crystalline tridymite and quartz. Disordered structure of this material is consequence of its genesis. Fast transition from liquid to solid state enables existence of dominant amorphous state. This is confirmed by X-ray analysis and optical transmission microscopy. Thermal treatment of the material at 1200oC causes higher degree of structure stabilization – crystallization of tridymite. The basic mass remains in the same disordered amorphous state, while the process of crystallization extends only in the zones with higher order degree. At the same time minimal changes occurs in the porosity, resulting in insignificant decreasing of specific surface area.